Microbial Group Specific Uptake Kinetics of Inorganic Phosphate and Adenosine-5′-Triphosphate (ATP) in the North Pacific Subtropical Gyre - Björkman, Karin M.; Duhamel, Solange; Karl, David M. (Frontiers in Microbiology, 2012)
We investigated the concentration dependent uptake of inorganic phosphate (Pi) and adenosine-5′-triphosphate (ATP) in microbial populations in the North Pacific Subtropical Gyre (NPSG). We used radiotracers to measure substrate uptake into whole water communities, differentiated microbial size classes, and two flow sorted groups; Prochlorococcus (PRO) and non-pigmented bacteria (NPB). The Pi concentrations, uptake rates, and Pi pool turnover times (Tt) were (mean, ±SD); 54.9 ± 35.0 nmol L−1 (n = 22), 4.8 ± 1.9 nmol L−1 day−1 (n = 19), and 14.7 ± 10.2 days (n = 19), respectively. Pi uptake into >2 μm cells was on average 12 ± 7% (n = 15) of the total uptake. The kinetic response to Pi (10–500 nmol L−1) was small, indicating that the microorganisms were close to their maximum uptake velocity (Vmax). Vmax averaged 8.0 ± 3.6 nmol L−1 day−1 (n = 19) in the >0.2 μm group, with half saturation constants (Km) of 40 ± 28 nmol L−1 (n = 19). PRO had three times the cell specific Pi uptake rate of NPB, at ambient concentrations, but when adjusted to cells L−1 the rates were similar, and these two groups were equally competitive for Pi. The Tt of γ-P-ATP in the >0.2 μm group were shorter than for the Pi pool (4.4 ± 1.0 days; n = 6), but this difference diminished in the larger size classes. The kinetic response to ATP was large in the >0.2 μm class with Vmax exceeding the rates at ambient concentrations (mean 62 ± 27 times; n = 6) with a mean Vmax for γ-P-ATP of 2.8 ± 1.0 nmol L−1 day−1, and Km at 11.5 ± 5.4 nmol L−1 (n = 6). The NPB contribution to γ-P-ATP uptake was high (95 ± 3%, n = 4) at ambient concentrations but decreased to ∼50% at the highest ATP amendment. PRO had Km values 5–10 times greater than NPB. The above indicates that PRO and NPB were in close competition in terms of Pi acquisition, whereas P uptake from ATP could be attributed to NPB. This apparent resource partitioning may be a niche separating strategy and an important factor in the successful co-existence within the oligotrophic upper ocean of the NPSG.